All the World's a Stage, and Sanctions the Merely Props: an Interactional Account of Sender-Target Dynamics in the Ukrainian Crisis. Issue 2 (15th March 2021) - Hofer, Alexandra
ABSTRACT: This article argues that sanctions are interactional tools; their interactive nature is evident if these measures are considered as a form of stigmatization, which is the outcome of an interaction between the group imposing the stigma and the actor that is stigmatized. Stigmatized states do not always accept the label that is placed upon them and can adopt strategies to counter or resist stigma. From a symbolic interactionalist perspective, this can be understood as a state's foreign policy role. Such an approach is illustrated through a study of Russia's response to being sanctioned by the EU and the US for its policies in the Ukrainian crisis. It is argued that Russian leaders are unlikely to cave into Western pressure because they reject the role of deviant that is placed upon their state and instead adopt the role of the 'untouchable' state, which is consistent with Russia's great power identity. Though the sanctions may enable the EU and the US to activate their roles as normative powers, in the context of the Ukrainian crisis, they have locked the parties into roles that contribute to the crisis' duration.